Oral health of Alzheimer's patients in Sao Jose dos Campos, Brazil - Machado, Miriane Carneiro; Lopes, Graziele Honorio; Marchini, Leonardo [UNESP] (Wiley-Blackwell, 2012)
Aim: Neglecting oral health can negatively affect the quality of life of Alzheimer's patients. This work evaluates the oral health of Alzheimer's patients in Sao Jose dos Campos, Brazil.Methods: Brazilian versions of the Oral Health Risk Assessment and Index to dental management of patients with Alzheimer's disease questionnaires were given to 50 patients (14 men, 36 women) diagnosed with Alzheimer's disease, with an average age of 79.7 years (SD = 9.2 years). Alternatively, the questionnaire was given to patients' caregivers. Cronbach's alpha test was applied to validate the Brazilian versions of these tests. Nonparametric tests were applied to test for possible associations.Results: Cronbach's alpha was 0.677. Nearly half of the patients (42%) presented with mild Alzheimer's disease, 38% moderate, and 20% severe. Most of the patients did not have their natural teeth (74%), had no oral health problems (64%), were on medication (92%), had not visited the dentist in the last year (70%), and had no need for urgent dental treatment (92%). of the 42% of patients who used dentures, 76.2% had been wearing the same dentures for over 5 years. There was no association between severity of disease and the presence of natural teeth (P = 0.346), use of removable dentures (P = 0.233), and the presence of oral health problems (P = 0.066).Conclusions: Patients with Alzheimer's disease have unmet oral health needs, but there was no association between severity of their disease and the presence of oral health problems. Geriatr Gerontol Int 2012; 12: 265-270.
Keywords: Alzheimer's disease; dental treatment; elderly; oral health; teeth